2006
DOI: 10.1088/0022-3727/39/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in CeFe2and Ru-doped CeFe2alloys

Abstract: The magnetocaloric effect (MCE) is studied in CeFe2 and Ru-doped CeFe2 alloys with dc magnetization measurements. The pure CeFe2 compound shows a distinct peak in MCE around the paramagnetic to ferromagnetic transition. In Ru-doped CeFe2 alloys there is a further transition from the ferromagnetic to antiferromagnetic state at low temperatures. This latter magnetic transition gives rise to a relatively large inverse MCE. A comparative study of the MCE associated with two different magnetic transitions is made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…Very recently, a similar MCE behavior has been reported in Ce͑Fe, Ru͒ 2 compounds, which is explained on the basis of the coexisting FM and AFM phases. 38 Based on the magnetic and neutron diffraction studies in Dy 2 Ni 2 Sn, which is isostructural to Gd 2 Ni 2 Sn and Tb 2 Ni 2 Sn, Penc et al 21 showed that the low temperature magnetic structure of this compound is noncollinear with large AFM and small FM components. The FM component is along the a axis, while the AFM component is in the ac plane.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, a similar MCE behavior has been reported in Ce͑Fe, Ru͒ 2 compounds, which is explained on the basis of the coexisting FM and AFM phases. 38 Based on the magnetic and neutron diffraction studies in Dy 2 Ni 2 Sn, which is isostructural to Gd 2 Ni 2 Sn and Tb 2 Ni 2 Sn, Penc et al 21 showed that the low temperature magnetic structure of this compound is noncollinear with large AFM and small FM components. The FM component is along the a axis, while the AFM component is in the ac plane.…”
Section: Resultsmentioning
confidence: 99%
“…Following the discovery of an enhanced MCE near room temperature in Gd [1], the search for other materials displaying a large room temperature MCE progressed rapidly, driven by the large energy saving and reduced environmental impact of magnetic refrigeration compared with traditional gas/ liquid refrigeration; such materials currently include Gd 5 (SiGe) 4 [2], FeMn P 1Àx As x [3], Ni 2 MnGa [4] and La(FeSi) 13 [5]. All of the listed materials have an MCEresulting from a first-order phase transition-greater than that of metallic Gd, with the accompanying magnetic entropy change being negative.…”
mentioning
confidence: 99%
“…For traditional magnetic refrigeration material, the wide working-temperature range always appears in bulk materials with two successive AF-FM and FM-PM magnetic transitions, like in Ce(Fe, Ru) 2 , Tb 2 Ni 2 Sn, or successively structural and magnetic transitions in Ni-Mn-In-based Hesular alloys (Chattopadhyay et al 2006;Kumar et al 2008;Zhang et al 2009). It is worthwhile noting that the signs of two entropy changes in most of these materials are opposite (Chattopadhyay et al 2006;Kumar et al 2008), which may not fully enlarge the working temperature range since the zero MCE may be not avoided in the transition temperature range between the conventional and inverse MCE. The exception is Ho 2 In compound that exhibits two successive magnetic phase transitions, in which two -DS M peaks with the same sign are partly overlapping, resulting in a wide temperature interval with appreciable MCE (Zhang et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The MCE is the isothermal change of entropy, which is from the variation of the magnetic moment, in a material because of an applied magnetic field (Chattopadhyay et al 2006). The variation of the magnetization of the nanoparticles/nanocapsules is determined by the applied field Zeeman energy, thermal agitation energy k B T, anisotropy energy barrier, and weaker interaction energy between the particles, which have different effects on the rotation of the moments, respectively.…”
Section: Resultsmentioning
confidence: 99%